2017
DOI: 10.1017/s0021932017000578
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Sex Composition of Living Children and Couples’ Agreement on Subsequent Fertility in India

Abstract: SummaryThe desire for children could be considered a reliable predictor of subsequent fertility. At the same time, the sex composition of surviving children, along with other demographic and socioeconomic factors, may affect a couple's fertility desire and, therefore, their subsequent fertility. This study examined the impact of the sex composition of living children and a couple's agreement on fertility desire on their subsequent fertility in India using data came from two rounds of nationally representative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…Middle and poor couples were less likely to have planned their fertility. This is in tandem with Kastor and Chatterjee (2018), who found that the odds of conceiving additional pregnancy or bearing another child were significantly lower among married women from rich households. This implies that poverty is a risk factor for unplanned fertility among couples in Nigeria.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Middle and poor couples were less likely to have planned their fertility. This is in tandem with Kastor and Chatterjee (2018), who found that the odds of conceiving additional pregnancy or bearing another child were significantly lower among married women from rich households. This implies that poverty is a risk factor for unplanned fertility among couples in Nigeria.…”
Section: Discussionsupporting
confidence: 63%
“…A couple might prefer and plan towards having another child, but of a different sex. Any child that deviates from that desired sex might end up unwanted and unplanned, and this may determine the further desire for fertility (Kastor & Chatterjee, 2018). This study draws attention towards the essence of studying the importance of child sex preference in couples' fertility desires, as also reported by Titilayo & Palamuleni (2015) in their study of unwanted fertility in Malawi.…”
Section: Discussionmentioning
confidence: 86%
“…Prior research has shown fertility-related attitudes to be predictive of their reproductive health behaviors and fertility ( Freedman et al, 1975 ; Hagewen & Morgan, 2005 ; Lightbourne, 1985 ). Several studies conducted in the South Asian context have identified strong associations between sex composition of children and fertility desire and other reproductive decisions including contraceptive use ( Calhoun et al, 2013 ; Chaudhuri, 2012 ; Edmeades et al, 2012 ; Jayaraman et al, 2009 ; Kastor & Chatterjee, 2018 ; Kumar et al, 2021 ; Stash, 1996 ; Yadav et al, 2020 ). However, most of these studies, focused on women's fertility preferences with very few studies considering men's fertility preferences alongside that of women.…”
Section: Introductionmentioning
confidence: 99%